Understanding land warfare - Tuck, Christopher, author.
1 online resource
Keywords: "This textbook provides a thorough grounding in the vocabulary, concepts, issues and debates associated with modern land warfare. The second edition has been updated and revised, and includes new chapters on non-western perspectives and hybrid warfare. Drawing on a range of case studies spanning the First World War through to contemporary conflicts in Syria, Ukraine, and Nagorno-Karabakh, the book explores what is unique about the land domain and how this has shaped the theory and practice of military operations conducted upon it. It also looks at land warfare across the spectrum of its conduct, including conventional campaigning, counterinsurgency, and peace support and stabilisation operations. Key themes and debates identified and analysed include: the tensions between change and continuity; the role of technology in land warfare; the relevance of culture and context; the difficulties in translating theory into effective military practice; in-depth discussions on issues of immediate contemporary significance, including hybrid warfare, emerging military technologies, and the military reform processes of the US, Russian, and Chinese land forces. This book will be essential reading for military practitioners and for students of land warfare, military history, war studies and strategic studies"--